Fishery, population characteristics and yield estimates of coastal tunas at Veraval - Ghosh, Shubhadeep; Pillai, N G K; Dhokia, H K (Indian Journal of Fisheries, 2016)
The fishery, population characteristics and yield estimates of coastal tunas Thunnus tonggol, Euthynnus affinis and Auxis thazard at Veraval were studied during 2003 – 2006. The average annual catch was 731 t, which contributed to 28% to the total gillnet catches. The main species of tunas landed were T. tonggol (46.8%), E. affinis (17.5%), Thunnus albacares (6.4%) and A. thazard (5.2%). E. affinis and A. thazard exhibited isometric growth but for T. tonggol it was allometric. The von Bertalanffy growth equation was Lt = 107.4 [1 – e - 0.18 (t + 0.0729)] for T. tonggol, Lt = 72.5 [1 – e - 0.56 (t + 0.0327)] for E. affinis and Lt = 46.6 [1 – e - 0.93 (t + 0.0153)] for A. thazard. The mortality rates M, F and Z for T. tonggol were 0.4, 0.72 and 1.12 respectively, while for E. affinis and A. thazard, the values were 0.94, 1.48 and 0.75 and 4.49, 1.69 and 5.97, respectively. The exploitation ratios for T. tonggol, E. affinis and A. thazard were 0.64, 0.44 and 0.75 respectively. The higher exploitation rate and lower MSY in T. tonggol and A. thazard was an indication of intensive fishing and overexploitation of these speceis. But for E. affinis, the exploitation rate was low and MSY was high indicating further scope for exploitation. Reducing the present fishing effort by 40%, maximum relative yield was realized for T. tonggol and A. thazard but for E. affinis, increasing the fishing effort by 80% provided the maximum relative yield.